Identification of young students’ metacognition in mathematical problem solving using the multi-method interview approach - Fazira, Shima Kunaza; Sukoriyanto; Rahardjo, Swasono (AIP conference proceedings, 2021)
Metacognition plays an important role in students’ mathematical problem solving. This study aims to describe the process of metacognition and metacognition components (awareness, evaluation, and regulation) developed by young students in solving mathematical problems. To describe young students’ metacognition clearly, this research uses descriptive qualitative method. This research was conducted with grade 5 students, since it aims to describe young students’ metacognition. Students were faced with problem solving and were asked to arrange an action card during the problem- solving process. Data analysis was performed based on the 4 results of selected action cards, with one subject each for a different set of action cards. The results show that young students have developed metacognitive behavior in solving mathematical problems, which are dominated by awareness and evaluation, while regulation is still not well developed. They also show different arrangements of metacognition component during the process of problem solving.